Tratamento pós-colheita em uvas e seus efeitos nos vinhos das variedades Chardonnay e Cabernet sauvignon - Leite, Tiago Trindade (2009)
Studies showed that the ultraviolet irradiation and the cold in woven of plants present some effect on the metabolism of phenolics compounds. The polyphenols are a group of substances present in the wine responsible for causing a series of benefits to the man's health and they are also important in the quality of the wine. The present work was proposed with the objective of comparing wines coming from grapes in wine varieties Cabernet Sauvignon and Chardonnay exposed to cold, ultraviolet irradiation and a subsequent storage, verifying their effects in the quality of wine through physiochemical analyses, biochemistries and sensorial. In the physiochemical analyses of the variety Cabernet Sauvignon were found small differences in the values of total acidity, however for the phenolics compounds, it happened larger variations, with the following results: Cold-irradiated 9723.3 mg EAG, Irradiated 6631.7 mg EAG, Cold-control 2696.7 mg EAG, Control 2258.3 mg EAG and Pattern 1150.0 mg EAG. In the determination of the % of inhibition of the antioxidant activity there were also significant differences, reflecting the same previous order with the following values: Cold-irradiated 97. 17%, Irradiated 88.50%, Cold-control 61.3%, Control 55.24% and Pattern 41.50%. For the variety Chardonnay, the values of the analyses physiochemical just obtained small differences in the pH, in the total and volatile acidity. For the values of the phenolics compounds, a larger variation was observed, where the values were: Cold-irradiated 91.44 mg EAG, Irradiated 76.06 mg EAG, Cold-control 70.13 mg EAG, Pattern 8.99 mg EAG and Control 8.94 mg EAG. Was observed in the determination of the % of inhibition of the antioxidant activity, that showed significant differences reflecting the same order previous with the following values: Cold-irradiated 91.35%, Irradiated 75.94%, Cold-control 70.67%, Control 24.13% and Pattern 9.13%. In the sensorial analysis of the wines of the two cultivate, just the trained panel of judges knowledgeable in wines distinguished the alterations correctly in the wines for the triangular test. The results demonstrate that the ultraviolet irradiation, the cold and the storage of the grapes increase the amount of polyphenols and antioxidant activity modifying the quality of the wine.